2013
DOI: 10.1080/1743873x.2012.758124
|View full text |Cite
|
Sign up to set email alerts
|

Diaspora tourists and the Scottish Homecoming 2009

Abstract: Since devolution and the establishment of the Scottish Government, the country has increasingly sought to engage with its diaspora, as part of its tourism strategy. In recent years, many countries have welcomed home their diasporas through organised events and in 2009, the Scottish Government organised a Year of Homecoming. This paper describes the experiences of some of the diaspora Scots who returned 'home' that year, and explores how returning 'home' had an impact on their knowledge of contemporary Scotland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…On this issue of reality versus awareness, previous research has shown that while many diaspora do indeed lack a strong awareness of the modern homeland, many are 'very perceptive' about contemporary issues (Sim and Leith, 2013). In this regard distance becomes a defining issue.…”
Section: Considering and Theorising Diasporasmentioning
confidence: 99%
“…On this issue of reality versus awareness, previous research has shown that while many diaspora do indeed lack a strong awareness of the modern homeland, many are 'very perceptive' about contemporary issues (Sim and Leith, 2013). In this regard distance becomes a defining issue.…”
Section: Considering and Theorising Diasporasmentioning
confidence: 99%
“…Numerous authors discuss what is variously called ‘roots tourism’ (Kalra & McLoughlin, ; Basu, ) or ‘nostalgia’ or diaspora tourism (e.g. Sim & Leith, : 260). These scholars link individuals' visits home to identity and a search for that identity – whether it is the first generation or the third or more searching for the identity.…”
Section: ‘Home Visits’: Slippages Of Transnationalism and Tourismmentioning
confidence: 99%
“…Added to these, the censuses allowed the governments a demographic and statistical picture-from 1801 these were purely summative, so as to give a snapshot each decade of population patterns, numbers of those engaged in agriculture or available for military service, for instance, and the exponential growth in population as the economy and agricultural production improved, as first shown by Malthus [7]. Censuses became genealogically useful-with names, ages, locations and additional details collected with increasing complexity from 1841 5 . The USA had a Federal Census each decade from 1790, but the first was essentially a head-of-household survey, and George Washington reportedly thought the final population size generated to be an underestimate.…”
Section: Motivations Of Genealogistsmentioning
confidence: 99%
“…Migrations, or participation in some historical event such as a rebellion, 3 Collected anecdotally and at classes over the past 20 years or so, and necessarily synthesised and simplified herein. 4 There is a literature of ancestral identity within various works on ancestral tourism, notably see [4][5][6]. 5 There are pre-1841 census "fragments" which have survived from various parts of Britain and Ireland, and there are extent censuses from (for example) some parishes in Midlothian, Scotland, dated 1790, 1811, 1821 and 1831. may seem like mass movements, but the individual motivations may not have been identical in every case, with a different assessment of "push" and "pull" factors acting on each person or family grouping.…”
Section: Motivations Of Genealogistsmentioning
confidence: 99%